Biodynamic Excisional Skin Tension Lines for Cutaneous Surgery - Paul, Sharad P. (Springer International Publishing, 2018)
This book is a detailed review of the 'state-of-the art' of skin lines in cutaneous surgery. Surgical literature is inundated with references to Langer's Lines, Cleavage Lines, Wrinkle Lines and Relaxed Skin Tension Lines, but this title discusses the difference between these and incisional and excisional lines biomechanically, introducing the concept of biodynamic excisional skin tension (BEST) Lines. The problem with current concepts of skin tension lines is that they seem to differ in different textbooks, and lines for surgical egress, which work in conditions of low tension, are not necessarily suitable for skin cancer surgery. Biodynamic Excisional Skin Tension Lines for Cutaneous Surgery describes skin biomechanics, the properties of collagen and elastin, lower limb skin vascularity and also maps BEST lines across the body, making it a great reference guide for plastic or dermatologic surgery worldwide. As such, it will be beneficial for anyone performing cutaneous surgery and skin cancer excisions in clinical practice, or for those planning further research into skin biomechanics to read this volume.